The Influence of Non-Formal Artistic and Creative Activities in Multicultural Educational Contexts - Pérez-Martin, Fernando (Revija za elementarno izobraževanje, 2017)
Our schools are becoming more and more multicultural every year. It is no longer uncommon to have in the same classroom students from over a dozen nationalities, with diverse backgrounds, beliefs and ways of seeing the world. This article is an invitation to reflect on the role that non-formal artistic and creative activities can play in multicultural educational settings. To this end, an excerpt from a Case Study carried out in one of Canada’s most multicultural schools is presented, showcasing some of the activities developed there and analysing the positive influences they have in its educational community.
Keywords: non-formal art; creativity; multiculural education; case study research; educational context